CO2 Elevation Accelerates Phenology and Alters Carbon/Nitrogen Metabolism vis-à-vis ROS Abundance in Bread Wheat - Padhan, Birendra K.; Sathee, Lekshmy; Meena, Hari S.; Adavi, Sandeep B.; Jha, Shailendra K.; Chinnusamy, Viswanathan (Frontiers in Plant Science, 2020)
Wheat being the foremost staple food crop across the world account for around 18-20% of human dietary protein. Recent reports suggest an exacerbating decline in wheat grain protein and ionome under CO2 elevation (CE). We have earlier reported that one of the mechanism behind decrease in N metabolites in wheat seedlings is the enhanced production of nitric oxide (NO) and the concomitant decrease in activity and transcript abundance of nitrate reductase (NR) and high affinity nitrate transporters (HATS) in CE. In the current study, two bread wheat genotypes differing in nitrate uptake and assimilation properties were evaluated for their response to CE. To understand the impact of low (LN), optimal (0N) and above optimal (HN) nitrogen supply on plant growth, phenology, shoot and root morphology, yield parameters, N and C metabolism, ROS and RNS signaling; plants were evaluated after short (hydroponics and pot experiment) and long term (pot experiment) exposure to CE and N levels. CE improved growth, altered N assimilation, C/N ratio, N use efficiency (NUE) and resulted in early flowering. In general, CE decreased shoot N content and grain protein concentration in wheat irrespective of N supply. Plants grown under CE displayed enhanced production of nitrosothiols and ROS and more so in HN. Photorespiratory ammonia assimilatory genes were down regulated by CE, whereas, expression of nitrate transporter/NPF genes were differentially regulated by EC, and N availability in different genotypes. The response to CE was dependent on N supply as well as genotype. Hence, N fertilizer regime needs to be revised based on these variables to tap the future CE scenario.